ANGKA BANDING KADAR ASAM URAT AIR KEMIH TERHADAP SERUM DI DIABETES MELITUS TIPE 2 (Ratio of Urinary Uric Acid Levels and Serum Uric Acid in Type 2 Diabetes Mellitus) - Amarensi Milka Betaubun; Fitriani Mangarengi; Ruland DN Pakasi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Diabetes Mellitus (DM) belongs to the group of metabolic diseases. The long-term complications of diabetes such as: diabeticretinopathy, neuropathy, and nephropathy, can be prevented or reduced by controlling the blood glucose levels. Impaired glucose tolerance,hypertension and dyslipidemia can decrease the disappearance from proximal tubules resulting in an increase in serum uric acid. The aimof the study to know the ratio of uric acid urine/serum in DMT2 with controls. This research study used a cross sectional study was andconducted on 35 samples of type 2 diabetes mellitus and 35 control samples of In- and Out-patient Clinics at the Dr. Wahidin SudirohusodoHospital, Makassar. The blood glucose, uric acid levels and urine uric acid were examined by ABX Pentra 400 (colorimetric method). Thenumber of DMT2 male patients was higher than females. Most of their age were between 50−54 years. The ratio of the urinary levels ofurine/serum UA was positively correlated to: age, sex, urine UA in DMT2 and control. Their data were analyzed with unpaired t test (p =0.00). This research showed that the ratio of urine/serum UA in DMT2 was 1.5 times than the controls. The results of this study showedan increase in the ratio of urinary levels of serum uric acid as 1.5 times higher than the controls.